Management of bhimal (Grewia optiva) planted on terraced field bunds in North Western Himalayas - BISHT, J K; SRIVASTVA, A K; GUPTA, H S (The Indian Journal of Agricultural Sciences, 2011)
Bhimal is an Important free which provldes nutritious fodder during winter uiionths and can be grown on wastelands. Cutting tiianagen?ent is very important for the tree growing along the cultivated fields. Management of bhimal ((Grewia optiva)planted on terraced field bunds in North Western Himalaya as studied at Research Farm of Vivekananda Palvatiya Krishi Anusandhan Sansthan, Hawalbag, Almora, Uttaranchal, (India). The expeiment as laid out in randomized black design with 4 replication and 4 treatments. Effect of cutting methods on forage, dry matter, fuel and protein yield of bhimal as found significant expect first year green forage y~cldS. urtabitiiy ofa particular cutting management was related to age of plantation. During initial 3 years coppicing gave the highest grcen forage yield (I 1.9, 14.7 and 16.8 kgltree in 1993 ,94 and 95 rcspectively). But, fourth years onwards pollarding at 2m height leaving main shoot intact gave the highest grecn forage yield except 1997 where it was lower than pollarding at 2 m height. Increase yield in this treatrilent is due to increase plant growth with the age. The highest protein content, i e 19% was found in the leaves of coppice treatment. Thus, korn the study it was concluded that bhi~nal combination of coppicing at initial and pollarding at latter stage was found to be optimum cutting mnanagement.